Better Students Ask More Questions.
Given f(x)= x^2 +3x-2 find f(m+1)
1 Answer | add yours
Best answer as selected by question asker.
We are given that f(x)= x^2 +3x-2 and we have to find f(m+1).
For this, substitute (m+1) for x.
Thereby we get:
f(x)= x^2 +3x-2
=> (m+1)^2 + 3*(m+1) - 2
open the brackets
=> m^2 + 1 + 2m + 3m + 3 -2
add the common terms
=> m^2 + 5m + 2
Therefore f(m+1) is equal to m^2 + 5m + 2.
Posted by justaguide on November 28, 2010 at 5:25 AM (Answer #1)
Join to answer this question
Join a community of thousands of dedicated teachers and students.